Exosome-mediated transfer of lncRNA HCG18 promotes M2 macrophage polarization in gastric cancer. (December 2021) - Xin, Lin; Wu, You; Liu, Chuan; Zeng, Fei; Wang, Jin-Liang; Wu, Deng-Zhong; Wu, Ji-ping; Yue, Zhen- Qi; Gan, Jin-Heng; Lu, Hao; Yuan, Yi-Wu; Zhou, Li-Qiang
Highlights: LncRNA HCG18 is highly expressed in Exos derived from GC and exosomal lncRNA HCG18 facilitate M2 macrophage polarization. Exosomal lncRNA HCG18 promotes M2 macrophage polarization by negatively regulating miR-875-3p in macrophages. Overexpression of miR-875-3p in macrophages restrains M2 macrophage polarization by decreasing KLF4 expression. GCCs-sh-HCG18-Exos restrain the tumor growth of GC induced by M2 macrophages. Abstract: Background: Gastric cancer (GC) derived exosomes (Exos) aggravate GC development by facilitating M2 macrophage polarization and long non-coding RNA (lncRNA) HCG18 was highly expressed in GC. This study aimed to investigate whether the exosomal lncRNA HCG18 regulated the M2 macrophage polarization in GC and the possible mechanism. Methods: The isolated GC cells (GCCs)-Exos were identified using transmission electron microscopy, Nanoparticle Tracking Analysis and Western blot. The GCCs-Exos function was verified by enzyme-linked immunosorbent assay and flow cytometry. Meanwhile, the exosomal lncRNA HCG18 function was determined using the in vitro assays. Furthermore, the underlying mechanism of the exosomal lncRNA HCG18 that regulated M2 macrophage polarization in GC was investigated using dual-luciferase reporter gene assay and RNA pull-down. Results: After the validation of GCCs-Exos, the GCCs-Exos facilitated the M2 macrophage polarization. The in vitro assays confirmed that the exosomal lncRNA HCG18 positively regulated the M2 macrophage polarization. Mechanistically, lncRNA HCG18 bound to miR-875-3p, miR-875-3p bound to KLF4. Furthermore, GCCs-exosomal lncRNA HCG18 elevated the KLF4 expression by decreasing miR-875-3p in macrophages to facilitate M2 macrophage polarization, thus alleviating GC. The in vivo assays clarified that the GCCs-exosomal lncRNA HCG18 restrained the tumor growth of GC induced by M2 macrophages. Conclusion: GCCs-exosomal lncRNA HCG18 elevated KLF4 expression by decreasing miR-875-3p in macrophages to facilitate the M2 macrophage polarization.